THE EFFECT USING STORY COMPLETION ON STUDENTS’ SPEAKING SKILL TO ELEVENTH GRADE STUDENTS OF SMK SWASTA YPIS MAJU BINJAI - Ainina Nurillah; Ayu Indari (STKIP Budidaya Binjai, 2021)
The research aims to find out the effect of using story completion on students’ speaking skill to eleventh grade students of SMK Swasta YPIS Maju Binjai at academic year 2020/2021. The problems that had been identified by the researcher are including that students were not interested in learning English. This research uses narrative text with oral test. This type of research is an experiment research. The populations of this research were students of the eleventh grade students of SMK Swasta YPIS Maju Binjai which consisted of five classes of the eleventh grade. The sample of the research consisted of 42 students. The study was an experiment and control research, the experiment class is XI TKJ and the control class XI AKL. The test was used in the pre-test and post-test. After that, the data has been computed by using t-test, it showed that tvalue was 11,797. The experimental class, standard deviation was 2, 81 and the control class, standard deviation was 2, 45. Then, after looking of distribution table value in certain degree of freedom (df), the result showed that the degree of freedom was 42 (n - 2 = 42-2 = 40). The value of table in line 40 was 2,021 at level significance 0, 05. This remarked that tvalue was higher than t- table (11,797 > 2,021). The hypothesis was accepted. It means that there was a significant effect of using story completion on students’ speaking skill to eleventh grade students of Smk Swasta Ypis Maju Binjai at academic year 2020/2021.